Acute Fatty Liver of Pregnancy - Alesha White; David B. Nelson; F. Gary Cunningham (Reproductive Medicine)
Acute fatty liver of pregnancy (AFLP), although rare, is a potentially fatal obstetrical disorder. It is characterized by acute liver failure of varying degrees with associated coagulopathy that occurs often in the third trimester of pregnancy. The following review discusses the history, etiopathogenesis, and subsequent clinical and laboratory findings that are associated with this disorder. It additionally attempts to aid in differentiating AFLP from other common obstetrical and non-obstetrical diseases with special emphasis on its differentiation from hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome. This review also discusses recommendations for delivery and postpartum care with focus on return to baseline and additional life-saving measures that may need to be pursued in the most difficult and refractory cases. Finally, it addresses maternal and perinatal outcomes associated with the disorder and the effect that this disorder can have on future pregnancies.